Effects of diazepam and flumazenil on food competition behavior in high- and low-aggression pigeons - Fachinelli, Carlos Cesar (2003)
The food competition interaction test performed with food-restricted pigeons with previously consolidated dominance is a useful tool for the study of offensive and defensive social aggression. In the present study, we examined the effect of GABA-A-benzodiazepine (BZD) receptor manipulation on aggression, emotion, feeder control, and eating behavior in high- and low-aggression female pigeons maintained at 80% of their normal weight and exposed to food competition interactions. The pigeons were divided into pairs by previously ranked high-aggression females (total time spent in aggression over 60 s/5 min; n=6 pairs) and low-aggression females (time spent in aggression less than 10 s/5 min; n=6 pairs). In Experiment 1, a pigeon in each pair of high- and low-aggression subjects were treated daily with an oral dose of diazepam (DZP, 0.6 mg/kg/0.3 ml) for 8 days. The other animal received the vehicle. On Day 8, food competition trials (10 min) were performed 30 min after treatments. In Experiment 2, pigeons were injected subcutaneously with flumazenil (FZL, 0.1 mg/kg/1 ml) or saline and exposed to a food competition trial 30 min after injections. In Experiment 3, one animal in each pair received DZP for 8 days. The other animal received the vehicle. On Day 8, the DZP-treated subjects were injected subcutaneously with FZL (0.1 mg/ kg/1 ml) 30 min before the oral dose of DZP. Trials were performed 30 min after DZP or vehicle administration. In Experiment 1, it was found that the DZP group of high-aggression pigeons showed lower scores of aggression (P<.05) and emotional responses (P<.05) than controls. The other group-scored behaviors were not affected. The DZP low-aggressions, however, showed scores of aggression eightfold higher than their controls (P<.05) but the other scored behaviors were not changed. In Experiment 2, FZL injection did not induce intrinsic effects on aggression either in the high- or in the low-aggression group. Experiment 3 showed that the emotional and aggressive responses to DZP were neutralized by FZL. This shows that GABA-A-BZD receptor mechanisms are implicated in the DZP responses in high- and low-aggression pigeons.